A trustworthy and energy-aware routing protocol in software-defined wireless mesh networks. (November 2017) - Lin, Hui; Hu, Jia; Xu, Li; Tian, YouLiang; Liu, Lei; Blakeway, Stewart
Highlights: A privacy-aware, secure and energy-aware green routing (PSGR) scheme was proposed. The PSGR defends against internal attacks and achieves strong privacy protection. The PSGR integrates a dynamic reputation mechanism and a key management protocol. Abstract: Hybrid Wireless Mesh Networks (HWMNs) were proposed to address the challenges in wireless communications to support mobile applications across different domains. Due to the multi-hop and decentralized network architecture, HWMNs are naturally susceptible to various security threats, especially internal attacks. Therefore, HWMNs must be able to detect anomalies, provide secure routing and protect user privacy through the cooperation among nodes. However, the existing routing protocols for HWMNs cannot ensure the security to protect the users privacy effectively. Moreover, traditional HWMNs are vertically integrated where the control and data planes of mesh routers are bundled together, which makes it complex and difficult to configure the network according to predefined security policies, and to adaptively respond to various dynamic security threats. Software-Defined Wireless Mesh Networks decouple the control plane and data plane of routers and thus enable a more flexible and efficient configuration of security policies. Taking up this opportunity to address the aforementioned challenges, this paper proposes a privacy-aware, secure and energy-aware green routing (PSGR) protocol that can defend against internal attacks, achieve stronger privacy protection and reduce energy consumption in Software-Defined HWMNs. The elaborate theoretical analysis verify that the PSGR protocol can implement the security and privacy protection against internal attacks effectively and efficiently. Simulation results demonstrate a superior performance of PSGR in terms of packet delivery ratio, network throughput and energy efficiency compared to the existing PA-SHWMP, PASER, and HWMP protocols in the presence of Blackhole/Grayhole attacks and wormhole attacks. Graphical abstract: